Linear trichilemmomas on the ankle of a 28‐year‐old female. (21st October 2016) - Gonzalez, Jessica L.; Plotnikova, Natalia; Seymour, Andrew; Mannion, Ciaran M.; Danialan, Richard; Rosmarin, David
Abstract : Trichilemmomas are benign cutaneous proliferations derived from the outer root sheath of the hair follicle. They most often occur on the head and neck region and show a female predominance. When multiple, they are associated with Cowden syndrome (CS), a rare disorder due to an autosomal dominant germline mutation in PTEN (phosphatase and tensin homolog on chromosome 10), a tumor suppressor gene. Trichilemmomas outside of the head and neck region are rare, and as such, the association with CS is not clear. A 28‐year‐old healthy female with no significant family history of cancer presented to her dermatologist with multiple erythematous papules on the left anterior ankle, starting at birth. A shave biopsy confirmed the diagnosis of trichilemmoma with focal desmoplastic features (or desmoplastic trichilemmoma). A PTEN immunohistochemical study showed patchy (but not complete) loss of staining of the lesional cells. After shave removal, the trichilemmomas recurred 1–2 months later.